BIOLOGICAL PECULIARITIES OF FALL WEBWORM MOTH DEVELOPMENT ON COMMON ASH IN ZHYTOMYR REGION - Bakalova, A.; Gritsyuk, N. (Scientific Progress & Innovations, 2021)
The authors of the article highlight the biological peculiarities of fall webworm moth development that is currently the most harmful of butterfly insects in gardens, roadside strips, forest belts and park areas. For the recreation of the population and other important elements of life, the community must take precautionary care of the global problem of fall webworm moth mass outbreaks. It is impossible to solve these important tasks, set before the ecological strategy of our country, without further development of science, because to destroy this phytophage, new technologies have to be and are developed. These technologies must be based on experimental parameters. In the authors’ opinion, the real way to solve this problem is possible only by management eco-balancing, where the main element should become the analysis of the growing number of fall webworm moth outbreaks in our regions. Therefore, a number of questions arise concerning the environment. And this means that there is a clear determination of trophic chains and these multifaceted mechanisms are important and imperfectly studied. That is why the authors conducted a long-term observation of fall webworm moth, the population of which was revealed in the problem regions of Andrushivka, Popilnia, Baranivka and Novohrad-Volynsky districts. As a result of the research, the reproduction table of the first phytophage generation was constructed. It negatively affects the common ash, primarily by the type of damage. This is the cobwebbing of the leaf apparatus in the form of nests, as 1-3 year old larvae live in groups. The population of common ash with larval nests varied significantly from29 to57 pcs/tree. The reproductive larval stage had a different result, correspondingly, so the larva of 2–3 years averaged from 11 to 8 pcs/nest. Moreover, the degree of fall webworm moth colonization on common ash in some districts made about 60–80 %.In terms of its harmfulness in Zhytomyr region, fall webworm moth phytophage occupies one of the first places, the greatest damage being caused by larvae. The larvae damage the leaf apparatus of the tree, eating it completely. As the process of photosynthesis stops, the root system suffers too much because of the lack of nutrients; and it is equally important that the age rings are not formed in the tree, which leads to hollowness where fungal formations develop and the tree shrinks.